How and much odes the housing market pay for environmental amenity? A Malaysian case - Abdul Hamid Mar Iman; Tan Yu Tian; Suriatini Ismail (2014)
There has been no empirical evidence of the importance of environmental amenity to house price reported from a developing market. This paper fills in the gap by taking the state of Terengganu, Malaysia as a case study. Based on the stated preferences for environmental amenity among potential home-buyers and 442 sale transactions recorded between 2006 and 2010, environmental amenity elements were included in the hedonic model of house price. The empirical results were generally consistent with those obtained from respondents’ feedbacks. This paper concludes that there is evidence to show that the housing market the study area places a significant importance of environmental amenity. As an implication, environmental amenity should remain as a major factor in a sustainable housing market in Malaysia.